Analisis Kualitas Pelayanan Alih Media Digital Pada Dinas Arsip Dan Perpustakaan Menggunakan Metode IPA - Audie Ehren; Nur Nawaningtyas Pusparini (Pusat Riset dan Inovasi Nasional, 2024)
Service quality is one of the important things for the Bogor district regional archives and library service, especially in the field of digital media transfer. Digital media transfer has an important role in saving files or archives. This research was created to measure the quality of digital media transfer services. Data collection in this research used a questionnaire distributed to residents who had used digital media transfer services. The questionnaire was distributed for 1 month and the author received 112 respondents. The questionnaire results were then processed using the IPA (importance performance analysis) method. From the results of the analysis of digital media transfer services, the conformity level is 82.11%, which means the quality of the services provided is quite good. Then, the results of the analysis of the IPA quadrants show that there are several things that need to be improved or maintained, which are focused on the first and second quadrants.